Genotypic Characterization of Azotobacteria Isolated from Argentinean Soils and Plant-Growth-Promoting Traits of Selected Strains with Prospects for Biofertilizer Production - Esteban Julián Rubio; Marcela Susana Montecchia; Micaela Tosi; Fabricio Darío Cassán; Alejandro Perticari; Olga Susana Correa (The Scientific World Journal)
The genetic diversity among 31 putative Azotobacter isolates obtained from agricultural and non-agricultural soils was assessed using rep-PCR genomic fingerprinting and identified to species level by ARDRA and partial 16S rRNA gene sequence analysis. High diversity was found among the isolates, identified as A. chroococcum, A. salinestris, and A. armeniacus. Selected isolates were characterized on the basis of phytohormone biosynthesis, nitrogenase activity, siderophore production, and phosphate solubilization. Indole-3 acetic-acid (IAA), gibberellin (GA3) and zeatin (Z) biosynthesis, nitrogenase activity, and siderophore production were found in all evaluated strains, with variation among them, but no phosphate solubilization was detected. Phytohormones excreted to the culture medium ranged in the following concentrations: 2.2–18.2 μg IAA mL−1, 0.3–0.7 μg GA3 mL−1, and 0.5–1.2 μg Z mL−1. Seed inoculations with further selected Azotobacter strains and treatments with their cell-free cultures increased the number of seminal roots and root hairs in wheat seedlings. This latter effect was mimicked by treatments with IAA-pure solutions, but it was not related to bacterial root colonization. Our survey constitutes a first approach to the knowledge of Azotobacter species inhabiting Argentinean soils in three contrasting geographical regions. Moreover, this phenotypic characterization constitutes an important contribution to the selection of Azotobacter strains for biofertilizer formulations.